ContractiveiMappings Having Mixed Finite MonotoneiProperty in GeneralizediMetric Spaces - Maibed, Zena Hussein (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
In thisipaper, we introduce the concepts of the modified tupledicoincidence points and the mixed finiteimonotone property. Also the existenceiand uniquenessiof modified tupled coincidenceipoint is discusses without continuous condition for mappings having imixed finite monotoneiproperty in generalizedimetric spaces.